Study Effecting of Halal Logo on Ready-to-eat Meal towards Purchase Intention of Non-Muslim Consumers In Bangkok - Bunnag, Tawisa; Kitikorn Dowpiset2 (AU Hybrid International Conference 2024 on " Entrepreneurship & Sustainability in the Digital Era" under the theme of "People Centric Knowledge in Intelligence World", 2021)
Purpose – This paper aims to determine the effects of halal logo on ready-to-eat meals toward purchase intention of non-Muslim consumers in Bangkok. The factors are halal awareness, halal logo and attitude, which are important factors in affecting the intention of consumers. Research methodology – Data were collected via a questionnaire with a sample of 230 non-Muslim consumers in Bangkok with non-probability sampling, convenience and snowball sampling method. Results – According to the research results, all factors positively impact non-Muslim consumers’ purchase intention towards ready-to-eat meal with the Halal logo. Additionally, the research found that non-Muslim consumers have positive attitudes and awareness of the Halal logo similar to those of the Muslim consumers. Although the study focuses on non-Muslim consumers, most of the respondents who participated in the research were Buddhists. Research limitations – The respondents were only limited to Thai nationality in Bangkok. The focus was only on Halal’s four variables: Halal awareness, Halal logo, attitude, and purchase intention. Recommendation – This research can support marketing to leverage the understanding of the Halal concept in the food industry to attract Muslim and non-Muslim consumers in domestic and international markets. Keywords Purchase intention, Attitude, Halal awareness, Halal logo, non-Muslim consumers, Ready-to-eat meals. Paper type Research paper